Latihan Drill sebagai Metode Efektif untuk meningkatkan Umpan Bawah pada Bola Voli di Sekolah Dasar: Drill Training as Effective Methods on Increasing Under-passing Ability of Elementary School Volleyball - Defrizal, Defrizal; Suharjana, Suharjana (Pedagogia : Jurnal Pendidikan, 2019)
This study aims to determine the effect of drill training methods and approaches to play with eye-hand coordination towards increasing under-passing volleyball. This study used . There was no comparison group in the design group. The population of this study was 40 female students who participated in volleyball extracurricular activities. Data analysis techniques used the Kolmogorov-Smirnov test for normality, homogeneity test and t-test to test hypotheses, samples correlated at a significance level of 5%. Test results show that there is a drill training effect on the ability to graduate. Hypothesis testing shows the value of t arithmetic (3.33)> t table (2,080), and p value (0,003) <0,05, indicating that Ho is rejected and Ha has been accepted means that there are significant differences in improving the ability to graduate after being treated. Based on the mean (mean) shows the average > pretest. These results can be concluded that there is a significant effect of drill training on increasing the under-passing ability of women's volleyball in SD 1 .